Loss coverage and stress testing mortgage portfolios: A non-parametric approach - Rodriguez, Adolfo; Trucharte, Carlos (Journal of Financial Stability, 2007)
This paper outlines the development of a practical approach to simulating a credit loss distribution function and to implementing a stress test exercise focusing on the entire Spanish mortgage portfolio. Specifically, we determine, via regression model, the main factors that explain why households fail to meet their mortgage payment commitments. This allows us to assign individual borrowers’ PDs and to estimate a rating system for the mortgage portfolio. Then, we simulate the empirical distribution function of mortgage loss rates using a Monte-Carlo resampling method, and compare the loss rates from this function with those provided by the Basel II IRB formulas. Finally, we assess, by running a stress exercise, the ability of banks to withstand certain adverse situations. The main result from this exercise is that, in general terms, Basel II IRB regulatory loss coverage offers fairly adequate protection for banks.